2005
DOI: 10.1007/s10350-005-0047-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Systemic Hypoxia on Colon Anastomotic Healing: An Animal Model

Abstract: This study validates a new animal model to study the effects of acute systemic hypoxia on colonic anastomotic healing. In this model, systemic hypoxia directly translated into local tissue hypoxia, and anastomotic healing was impaired. Contrary to our original hypothesis, hypoxia led to a significant increase in vascular endothelial growth factor and inducible nitric oxide synthase protein expression at the colonic anastomotic site. Impairment in anastomotic integrity despite upregulation of these angiogenic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 43 publications
(61 reference statements)
1
79
0
4
Order By: Relevance
“…At the molecular level of angiogenesis, vascular endothelial growth factor (VEFG) and nitric oxide (NO) are the two key factors that are relevant [30] . Tan-no et al reported the anti-inflammatory effect of propolis through inhibition of nitric oxide production [31] and also Attard et al reported the expression of both VEGF and inducible nitric oxide synthase (iNOS) significantly increased at the anastomotic site exposed to a hypoxic environment but the healing was not enhanced [32] . These two hypotheses above warrant further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level of angiogenesis, vascular endothelial growth factor (VEFG) and nitric oxide (NO) are the two key factors that are relevant [30] . Tan-no et al reported the anti-inflammatory effect of propolis through inhibition of nitric oxide production [31] and also Attard et al reported the expression of both VEGF and inducible nitric oxide synthase (iNOS) significantly increased at the anastomotic site exposed to a hypoxic environment but the healing was not enhanced [32] . These two hypotheses above warrant further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Interposition of bioengineered substitutes organized in a tubular fashion, such as the gut, appear to be particularly prone to complications (Badylak, S. et al, 2000;Chen & Badylak, 2001;Thompson et al, 1986). Given that inadequate oxygen supply and decreased local microperfusion are believed to be at the origin of many adverse events in gastrointestinal surgery (Anegg et al, 2008;Attard et al, 2005;Sheridan et al, 1987), hypoxia and ischemia presumably account for anastomotic leakage and stricture formation after interposition of bioengineered tubular constructs. In recent years, considerable effort has been done to develop bioreactors that allow nourishment of growing tissue masses in vitro whose size exceeds the largest possible unit accessible to oxygen and nutrients by sole diffusion.…”
Section: Bioreactorsmentioning
confidence: 99%
“…13,14 Similarly, hypoxia has been reported to suppress wound healing in various tissues, including the lung. [15][16][17][18] Because the surface of the injured lung is immediately adjacent to the pleural cavity, we reasoned that the intrapleural gaseous milieu could influence lung healing and resolution of air leaks. Specifically, we hypothesized that intrapleural hypercarbia would be associated with prolonged PAL.…”
mentioning
confidence: 99%